Microlearning-based media of probability: An innovative student worksheet - Novi Komariyatiningsih; Yusuf Hartono; Ratu Ilma Indra Putri; Cecil Hiltrimartin (Universitas Hamzanwadi, 2025)
The constraint on reasoning ability among Indonesian mathematics students is a pressing issue. Several study results show that students' low mathematical reasoning is due to a lack of conceptual understanding of the material being studied. Probability is one of the materials that can help mathematical reasoning. There is a sample space that requires students' reasoning ability to determine all possible outcomes. This study aims to design a microlearning-based learning on probability material using the culinary tourism context of Prabumulih City that is integrated into student worksheet, which is valid and practical to help students learn the probability in phase E and train their reasoning skills by PMRI (Indonesian Realistic Mathematics Education). This study was a qualitative method of development study type, consisting of two stages: preliminary study and formative evaluation. The subject of this study was 36 tenth-grade. The data collection techniques were observation, tests, and interviews, which were analyzed descriptively. This research produced a student worksheet that was valid and practical and integrated with microlearning media (comic, video) on probability material using the culinary tourism context of Prabumulih City, Indonesia. Based on data analysis, this worksheet can improve students' conceptual understanding and reasoning abilities.